2006
DOI: 10.1682/jrrd.2006.05.0054
|View full text |Cite
|
Sign up to set email alerts
|

Persistent problems after traumatic brain injury: The need for long-term follow-up and coordinated care

Abstract: Persistent problems after traumatic brain injury: The need for long-term follow-up and coordinated careTraumatic brain injury (TBI) is one of the leading causes of death and long-term disability in the United States [1]. Survivors of TBI experience various problems, including physical, cognitive, emotional, and community integration issues. Established in 1992, the Defense and Veterans Brain Injury Center (DVBIC) coordinates nine healthcare centers-two civilian, three military, and four Department of Veterans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 5 publications
3
54
0
Order By: Relevance
“…When entered into the same model simultaneously along with other factors, each remained a significant predictor, with mTBI history the most robust. PTSD and depression have been well documented in OIF/OEF veterans [6,23,[48][49][59][60][61][62][63][64][65][66][67]. This is a notable finding because other studies have found diminished effects of TBI when PTSD and depressive symptom severity were taken into account [6,62].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…When entered into the same model simultaneously along with other factors, each remained a significant predictor, with mTBI history the most robust. PTSD and depression have been well documented in OIF/OEF veterans [6,23,[48][49][59][60][61][62][63][64][65][66][67]. This is a notable finding because other studies have found diminished effects of TBI when PTSD and depressive symptom severity were taken into account [6,62].…”
Section: Discussionmentioning
confidence: 97%
“…Because of the degree of symptom overlap between TBI and psychiatric disorders [46,61,[63][64]66,[76][77][78][79][80], clinicians evaluating TBI also should determine whether mental health conditions are present to decide on the best course of treatment [6,62]. Patients with MSI may benefit from a team-based approach to care [63][64][77][78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most disruptive symptoms experienced by TBI patients who survive their injuries are persistent memory deficits. [1][2][3] These deficits include declarative memory and working memory dysfunction that are caused by damage to the hippocampus. [4][5][6][7][8][9][10][11] Problems with memory can interfere with post-TBI recovery, rehabilitation, and living an independent life.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the conflicts in Iraq and Afghanistan have resulted in a new generation of combat survivors who frequently have complex physical injuries and emotional trauma [3][4][5][6]. The Department of Veterans Affairs (VA) healthcare system has often been acknowledged for its exemplary care of veterans.…”
Section: Introductionmentioning
confidence: 99%